Chesapeake Gold : Man and Oyster on the Bay - Brait, Susan, 1943- (Book collections on Project MUSE., 2015)
The figure of an old man poling a skiff toward shore against the evening light engaged Susan Brait to learn about Chesapeake Bay, and it is that image which opens this her book on the oystermen of the Bay and the sapping of their traditional life, and even the bounty of the Bay itself, by the demands of American society. With directness and poetic economy Brait takes the reader into the life of the Bay and into the complex relationships that affect oysters and those who make their living from them. Her account weaves easily from the daily work of oystermen to the natural forces that have shaped.